2022
DOI: 10.1007/s00125-022-05704-7
|View full text |Cite
|
Sign up to set email alerts
|

Health impact of seven herpesviruses on (pre)diabetes incidence and HbA1c: results from the KORA cohort

Abstract: Aims/hypothesis The prevalence of type 2 diabetes is increasing worldwide, and previous studies have suggested that it is higher in individuals who are seropositive for herpesviruses. This study examines the prospective association of herpesviruses with (pre)diabetes to evaluate their potential role in diabetes aetiology. Methods Two follow-up examinations of the German population-based KORA cohort (F4 and FF4) were used to identify participants with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Body mass index (BMI) correlated significantly with HbA1c levels, as expected, but interestingly, a significant positive correlation was also observed between HbA1c levels and HSV seropositivity, in line with a recent population-based study reporting a possible link between HSV type 2 infection and prediabetes. 18 In a multiplex analysis of 48 cytokines, we found plasma concentrations of several pro-inflammatory chemokines, such as CCL27, CXCL9, and CXCL10, to increase with age (Fig. 1D).…”
Section: The Resist Senior Individuals Cohortmentioning
confidence: 84%
“…Body mass index (BMI) correlated significantly with HbA1c levels, as expected, but interestingly, a significant positive correlation was also observed between HbA1c levels and HSV seropositivity, in line with a recent population-based study reporting a possible link between HSV type 2 infection and prediabetes. 18 In a multiplex analysis of 48 cytokines, we found plasma concentrations of several pro-inflammatory chemokines, such as CCL27, CXCL9, and CXCL10, to increase with age (Fig. 1D).…”
Section: The Resist Senior Individuals Cohortmentioning
confidence: 84%
“…Over the 5-year follow-up, new-onset cases were significantly higher in the group with CMV disease compared to case controls. 9 Other studies have also shown relationships between seropositivity for CMV and T2D 10,11 and with pre-diabetes incidence, 12 even in the absence of CMV disease per se. As studies of CMV pathogenesis are a significant research focus at our institution, 13 we have serology on hundreds of animals that can be used to address this question.…”
Section: Cytomegalovirus (Cmv) Statusmentioning
confidence: 98%
“…In human studies, it was shown that acute hyperglycemia impaired IL-6 and IL-17 expression, particularly in CD14+CD16+ intermediate monocytes [ 77 ]. More recently, it is widely believed that consumption of a “Western diet” (i.e., high in refined carbohydrates and saturated fats) contributed to both incidence and mortality during the COVID-19 pandemic [ 78 ], while recent support for a link between HSV and type II diabetes is also noteworthy [ 79 ].…”
Section: Supplements and Natural Productsmentioning
confidence: 99%